The synthesis of potential analgesics derived from thebaine - Michael Burton (1979)
The thesis describes the synthesis of novel bridged thebaine derivatives with heterocyclic rings attached to C-7 and a study of the associated chemistry. Use has been made of the α-hydrazide (3) formed from the α-ester (2), itself prepared by Diels-Alder addition of methyl acrylate to thebaine (1). From this hydrazide, either directly or via other novel open-chain precursors, three new heterocyclic ring systems attached to the 6,14-endoetheno-6,7,8,14-tetrahydrothebaine moiety (T) have been obtained. These are the α- and β-1,2,4-triazines (4 and 5), the 1,2,4-triazol-5-thione (6) and the 1,3,4-oxadiazole (7). [Continues.]